Levels of depressive and anxious symptoms of pregnant women before vs. during the COVID-19 pandemic. (13th April 2021) - Barros, M.; Aguiar, M.; Macedo, A.; Azevedo, J.; Pereira, A.T.
Abstract : Introduction: The effects on the population's mental health due to the rapid global spread of COVID-19 are even greater for specific groups such as pregnant women. Objectives: To compare levels of depressive and anxiety symptoms of pregnant women before vs. during the COVID-19 pandemic and to analyze the role of COVID-19 fear in perinatal psychological disorder. Methods: 200 Brazilian women evaluated during the pandemic in May-June 2020 (Sample-1) with the Brazilian Covid-19 Fear Scale for the Perinatal Period (Barros et al. 2020) and Screening for Perinatal Depression and the Perinatal Anxiety Crawl Scale, both with α> .90. Sample-1 was compared with a sample of 300 Portuguese women; these responded to the same questionnaires, before the pandemic, in 2017 and 2018 (Sample-2). Results: Sample-1 had significantly higher mean scores of depression (52.73 ± 20.26 vs. 35.87 ± 16.98, t = 10.77, p <.001) and anxiety (36.58 ± 18.23 vs. 18.50 ± 13.71, t = 11.94, p <.001) and correlated significantly (p <.05) and moderate (r.30) with the fear of COVID-19. Hierarchical regression analyzes showed that, even after controlling for the effect of risk factors for PPP (Pereira et al. 2020), fear of COVID-19 is a significant predictor of depressive symptomatology levels (increments of 2-5%) and anxious (10-15%) during the pandemic. Conclusions: The Sample-1 being from a different country may be a confusing factor, however, the magnitude of differences in PPP levels and the relevant role of fear in COVID-19, alert us to be aware of perinatal mental health.